Quantitative decision making in land banking: a Monte Carlo simulation for China's real estate developers - Bao, Haijun; Chong, Alain Yee-Loong; Wang, Hongdi; Wang, Liyuan; Huang, Yikun (International Journal of Strategic Property Management, 2012)
The real estate industry is one of the fast growing industries in many developing countries such as China and India. The Chinese real estate industry has gone through many reforms from offering housing as part of its social welfare system, to the current capitalist model based on demand and supply. Due to these reforms and the shortage of lands for development in China's urban cities, many Chinese property firms have resorted to land banking in order to secure land property for future developments. However, in China, land speculation is considered illegal, while failure to purchase the suitable land for future developments will hinder the real estate developers’ future business and growth. The purpose of this paper is to develop a decision making model for property developments in their land banking decisions and strategies. The paper employed mathematical modeling and Monte Carlo simulation to examine our decision model, and further validated our results by conducting the simulation by using China Vanke Co. Ltd as a case study. This study is one of the first few studies that develop a decision model for land banking in China. It also helps real estate enterprises to make rational and dynamic decision in the current dynamic property market.First Publish Online: 19 Dec 2012